THE PATHO-PHYSIOLOGY OF HYPERCALCEMIA - Kanis, J; Cundy, T; Heynen, G; Russell, R (1980)
There are many causes of hypercalcaemia, all of which are characterised by abnormalities in the transport of calcium across gut, bone, kidney or a combination of these. It is possible to separate the relative importance of these factors in individual patients which not only help the clinician to understand the pathogenesis of hypercalcaemla but should also influence the therapeutic priorities. © 1980.